Tillich's Theodicies. (13th September 2022) - Shearn, Samuel Andrew
Abstract: This essay explores the development of Tillich's writings on the relationship between divine providence and suffering, and his approach to theodicy. First, I attend to the various stations of his early life and his earliest writings in various genres. Here we see the instrumental‐pedagogical theodicies of his student days and earliest preaching give way to an increased emphasis on the suffering of God. However, unlike many twentieth century theologies of suffering, Tillich retains a strong teleological notion of divine providence, even in the face of the horrors of the First World War. Second, I analyse Tillich's American systematics and sermons against the background of his early writings, characterising his writings as a Hegelian approach to suffering, subsuming the individual under the teleology of divine creativity.